A study on trip generation in University Malaysia Pahang, Pekan - Nurhidayatul Akhma, Mat Roka (2017)
Nowadays, people are busy engaged themselves into a lot of activities in their domestic life. These activities which are include going to school and work, had become their daily routine regardless the morning or evening. Their daily activities are very dependent on the condition and level of traffic’s service in the transportation system that are available in the areas. Therefore, numbers of vehicle on the road are increasing rapidly each year because of improvement in economy and growth of population. This situation also happens in the study area, University Malaysia Pahang, Pekan which it will give impact on traffic problem such as parking problem and traffic congestion. In order to avoid this kind of problems often occurred in the research area, this study on trip generation is conducted. The objective of this study is to determine behavior of trip makers in and out UMP, and trip generation rate in term of population. All the data such as types of vehicle used, modes of travel and number of population are collected for trip generation data. The data will be analyzed and shown by using bar chart and graph. New transportation policy planning and engineering will be developing in a relationship between trip end production or attraction and land use in the future.